New cumacean species (Crustacea: Peracarida) from Salomon Islands - Corbera, Jordi (Zootaxa, 2008)
Four new species of Cumacea are described from deep-sea samples collected around Salomon Islands during the French campaign SALOMON I. Bathylamprops pagesi sp. nov. and Bathylamprops caperatus sp. nov. belonging to the family Lampropidae differ from the all currently known species by the oblique lateral carina running from anterolateral angle backwards. The nannastacid Campylaspis alisae sp. nov. can be identified by the shape of the carapace carinae, especially in dorsal view. The diastylid Oxyurostylis? salomonensis sp. nov. due to the lost of the telson tip, is difficult to assign either to the genus Diastylis Say, 1818 or to the genus Oxyurostylis Calman, 1912. At the moment, it is included provisionally to the genus Oxyurostylis and it differs from the other species in the genus by its flattened eyelobe and the higher number of setae on telson.